SISTEM E-FILING SEBAGAI UPAYA DIREKTORAT JENDERAL PAJAK DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK E-FILING SYSTEM AS A GENERAL DIRECTORATE OF TAXES EFFORTS IN INCREASING TAXPAYERS COMPLIANCE - Bq. Anggun Hilendri; Sapto Hendri BS (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This study seeks to provide an overview of the use of information technology carried out by individual taxpayers in this case the State Civil Apparatus in fulfilling their tax obligations through the taxation information system developed by the General Directorate of Taxes. This study aims to determine the compliance of the State Civil Apparatus taxpayers who are registered with the Pratama Praya Tax Service Office in reporting their tax returns using e-Filing. The existence of a system provided by the General Directorate of Taxes can improve taxpayer compliance, especially State Civil Apparatus individual taxpayers because it is now easier to carry out tax obligations, namely reporting tax returns without having to queue at the Tax Service Office especially the Praya Pratama Tax Office so that tax administration runs effectively and efficiently. Data transmission of Notification Letter can be done anywhere and anytime, where the data will be sent directly to the database of the General Directorate of Taxes with internet facilities that are distributed through the website of the General Directorate of Taxes. But in reality the process to make taxation efficient through e-Filing facilities is not as easy as imagined, for example the difficulties experienced by taxpayers in entering their tax document data because there are still many taxpayers who do not fully understand how to submit tax returns electronically available on services the website of the General Directorate of Taxes. Therefore, the socialization to taxpayers, especially the State Civil Apparatus, was further increased so that there was an increase in the compliance of taxpayers from year to year.